The relationship between entrepreneurial characteristics and their impact on organizational success, field research in Karbala governorate hotels (مجلة المنصور, 2023)
The current research aims to analyze the five Dimensions personality of the employees according to the Model (FFM), and disclose to what extent their impact on the self-belief, and to what extent they believe in values, ideas and principles. Making a test as to know and to identify the type and level of relationship correlation and impact for the research variables Represented by personality dimensions as an independent variable, and self-beliefs package as a dependent variable, the research comes to contribute to knowing and understanding behaviors of Individuals employees and predicting them. The Ministry of Science and Technology was a research community to apply the practical aspect. The results of the first hypothesis indicated (that there is a positive, significant correlation between the total five personality dimensions and the self-belief package as a whole). The second hypothesis showed (a positive impact relationship for the five personality dimensions on the overall level in the self-beliefs package as a whole). The conclusions came to confirm that (the organization in question) possesses a good percentage of workers who have the ability to open up to others to increase knowledge and develop capabilities, and therefore the dimension of openness to experience is the most closely related dimension among the five personality dimensions to the package of self-beliefs.